The European Size Distribution of Firms and Employment - Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2006)
The policy debate in recent years has increasingly focused on issues concerning size distribution of firms and employment. It is often claimed that we are approaching a new economic era where large enterprises have lost their importance in developed economies. This raises the question of what we can say about the size distributions on the basis of currently available European data. How important are large enterprises and can we detect any changes with regard to their importance? How do countries of the European Union differ in this regard? How reliable is available data ? does it permit us to draw any conclusions? Examining the availability and quality of data on European firm size and employment, we find that the existing data is severely limited in a number of respects. Conclusions based on the currently available data must hence be interpreted with considerable caution. However, recent measures by for instance the European Union will greatly improve the availability and quality of firm size data in the future.
Keywords: L11; O52; 330; Business Structure; Industrial Structure; Size Distribution; Small and Medium Sized Enterprises; Betriebsgröße; Betriebsgrößenstruktur; Beschäftigung; KMU; EU-Staaten